Proceedings of the University Alliance Executive Directors Workshop: ECIS 2001 - Jörg Becker (Westfälische Wilhelms-Universität Münster, Institut für Wirtschaftsinformatik, 2001)
The introduction of Enterprise Systems (ES) into the curriculum at Business and IS Faculties and Schools is for many universities a major challenge. However, this problem is in various aspects of special nature: the students' demand is enormous and in many cases productfocused, Enterprise Systems are typically very comprehensive and complex, and knowledge about ES is often missing. By the time textbooks of satisfying quality are available, there are new systems' upgrades and innovation cycles to deal with. The Queensland University of Technology (QUT) is comprehensively using the market leading Enterprise System SAP R/3 within its curriculum and is also conducting research in this area. This paper briefly reports on the activities and experiences at QUT, which is now one of the few world-wide mySAP University Application Hosting Centers. The public demands a close cooperation between universities and companies in order to improve the quality of students' education and to speed up the transformation process from theoretical ideas to products. This paper describes a successful cooperation between a university research project and a company. We show that both partners of the cooperation have numerous benefits. The following case study is the point of reference for an analysis of an existing cooperation. A data warehouse research project for higher education at the University of Bamberg (CEUSHB) exemplifies the university's part of this cooperation. The business intelligence company Microstrategy is the other partner outlined in the paper. Oracle has introduced in 1998 the OAI program to tackle the IT labour crisis. Since then over 150,000 students have been involved in courses in over 40 countries. This paper describes the components of the program and the benefits for all sides. The program is finally reviewed from an academic perspective and cornerstones of a successful strategic partnership are defined. The availability of decision support and productivity software is providing the opportunities for smaller manufacturing or non-manufacturing companies to develop systems which utilize operations research models to support decision-making and address issues such as product mix, efficient production methods, network flow optimization, inventory and stock management, resource scheduling and capital allocation. The model of such a business decision support system, which incorporates linear and integer programming, is presented. The system is based on the SAS software which has been widely used in operations research area. The graphic user interface (GUI) is developed to assist users in making effective management decisions without requiring extensive technical training. Some decision making problems in an integrated production management context are pointed out and a simple example of product-mixed problem is shown to illustrate the usage of the decision support system in a practice.
Keywords: 650